Exploring The Signified and Signifier in Song Lyrics through A Saussurean Semiotics Lens - Ramdani, Sandy Muhammad; Sakinah, R. Myrna Nur (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2023)
Song Lyrics are supposed to have some sort of an implied meaning or another meaning that the performer tries to convey. In this study, the signifier and signified of Taylor Swift's song lyrics will be dissected and examined. For the purpose of this investigation, a qualitative methodology will be utilised, and a semiotic analysis developed by Ferdinand de Saussure will be applied to each verse of the song lyrics. In his theory, Saussure proposed that in order for something to be considered a sign, it needed to include both a marker, also known as a signifier, and a concept (Signified). For the aim of collecting data for this analysis, the song will be sectioned off into stanzas, and each each stanza will be assigned a signifier. Afterward, the provision of a signified, more especially the notion of the marker. Lastly, the researchers will then determine the love meaning of each stanza as well as each verse. Keyword: Lyric, Saussure Semiotics, Taylor Swift